The Urgency of Regulating Elements of Community Participation In The Toll Road Investment Process In Indonesia - Simon, Simon; Eddy, Triono; Ramlan, Ramlan (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
The development of toll road infrastructure in Indonesia represents one of the national government's strategic priorities to accelerate economic growth, improve connectivity, and enhance regional mobility. Nevertheless, the success of toll road investment projects cannot be measured solely from government policies or investor commitments, but also relies heavily on the involvement and active participation of the community as key stakeholders. Community participation plays a vital role in ensuring the transparency, accountability, legitimacy, and sustainability of toll road projects, particularly considering their significant social, economic, and environmental impacts. This study aims to examine the necessity of regulating community participation elements in the toll road investment process in Indonesia. The research employs a normative juridical method, combining a statutory and case approach, with a focus on legal provisions, policy frameworks, and practical experiences. The findings indicate that the current regulatory framework governing public participation remains fragmented, sectoral, and insufficient in guaranteeing inclusivity and fairness. Therefore, more precise, comprehensive, and enforceable regulations are urgently needed to strengthen public involvement mechanisms. These should include structured consultation forums, open and timely access to information, as well as adequate protection of rights and compensation for affected communities. By institutionalizing such participatory mechanisms, toll road investments can be developed within an inclusive legal framework that not only ensures justice for communities but also fosters investor confidence and project sustainability. Ultimately, embedding community participation in toll road investment regulations will contribute to the long-term success of infrastructure development and support Indonesia’s vision of equitable, sustainable, and participatory economic growth.